Análise da relação dos indicadores lucro/preço e valor contábil/preço com o retorno de ações e crescimento do lucro das empresas brasileiras - Jureves, Renan Couto (2019)
Financial statements are essential for asset pricing of a company. Fama and French (1992) have demonstrated with multifactorial models that size and book-to-market (B/P) explain stock returns. Penman et al. (2018) suggested that the unlevered variables and financial leverage explained stock returns. The objective of this dissertation is to study the relationship between the accounting and market variables with the earnings growth and stock returns, as well as the relationship between financial leverage and unlevered variables with stock returns. I perform a cross-section study with 161 shares of companies from IBRX100 and small caps indexes in the Brazilian stock exchange collected during the period from 2011 to 2016. Three analyzes were performed using linear regression to relate the dependent variables (earnings growth and returns) with predictor variables (B/P, earnings/price E/P, size, market beta and unlevered variables). Our results indicated that earnings growth presented a positive relation with E/P. Moreover, stock returns had a negative relation with B/P and unlevered B/P, and a positive relation with unlevered E/P and size. Financial leverage did not present significant results to explain earnings growth and stock returns.